From Materia Medica to the Pharmacopoeia: Challenges of Writing the History of Drugs in India. Issue 4 (April 2016) - Bhattacharya, Nandini
Abstract: Historians of indigenous medicine in colonial India have looked more closely at the changes, reinventions and reformulations of institutions of Ayurveda and Unani than at the cognitive content of the drugs themselves. The few historians who have examined the changing content of indigenous medicines have conceptualised the creation of materia medica of Indian drugs through two tropes: one of circulation (of specific drugs) through epistemological and geographic boundaries and the second, of marginalisation of certain other drugs either through a lack of textual legitimacy or the lack of the newly discovered 'active principles' within each drug. While these approaches have been useful, there is a case to be made for understanding the creation of formularies of Indian drugs in 19th and 20th centuries through the prism of medical praxis in India.